The Influence of Product Quality, Halal Labels, and Social Media Marketing on Purchasing Decision of Somethinc Products Study on Generation Z Consumers - Nabila Khairunnisa; Andyan Pradipta Utama (Jurnal Ilmiah Manajemen dan Bisnis, 2026)
This study aims to test and analyze the effect of product quality, halal labels and social media marketing on purchasing decisions of Somethinc products in Generation Z consumers. Sampling in this study used the Purposive Sampling Technique with a sample size of 180 respondents. This study is a quantitative study with a data collection method through a Google Form questionnaire, and analyzed using the Structural Equation Modeling (SEM) method using SmartPLS 3.0. The results showed that product quality had a positive and significant effect on purchasing decisions, halal labels had a positive but not significant effect on purchasing decisions, social media marketing had a positive and significant effect on purchasing decisions.